Myocardial Opioid Receptors in Conditioning and Cytoprotection - Grant Williams-Pritchard; John P. Headrick; Jason N. Peart (MDPI AG, 2011)
Opioid compounds and G-protein coupled opioid receptors (ORs) have been studied widely in terms of central nervous system (CNS) actions relating to pain management and drug abuse. Opioids are also linked to induction of mammalian hibernation, a natural state of tolerance involving prolonged and orchestrated shifts in cellular metabolism, growth and stress resistance. It is not surprising then that OR agonism induces acute or delayed cytoprotective states in myocardium, rendering ORs an attractive target for protection of cardiac tissue from the potentially fatal consequences of ischemic heart disease. Cardiac ORs are implicated in triggering/mediating so-called 'conditioning' responses, in which powerful cytoprotection arises following transient receptor ligation prior to or immediately following ischemic insult. These responses involve one or more OR sub-types engaging pro-survival kinase cascades to ultimately modulate cell stress and mitochondrial end-effectors. However, important questions remain regarding the role of endogenous opioids, OR signalling, and the transduction and mediation of these protective responses. We briefly review opioid-mediated cardioprotection, focussing on recent developments in signal transduction, the role of receptor 'cross-talk', and the effects of sustained OR ligand activation.